Transition Metal-Carbon Bond Enthalpies as Descriptor for the Electrochemical Stability of Transition Metal Carbides in Electrocatalytic Applications - Gohl, Daniel; Ruess, Holger; Pander, Marc; Zeradjanin, Aleksandar R.; Mayrhofer, Karl; Schneider, Jochen M.; Erbe, Andreas; Ledendecker, Marc (Journal of The Electrochemical Society, 2020)
Transition metal carbides are used for various applications such as hard coating, heterogeneous catalysis, catalyst support material or coatings in fuel cell applications. However, little is known about the stability of their electrochemically active surface in aqueous electrolytes. Herein, the transition metal-carbon bond enthalpy is proposed as stability criterion for various transition metal carbides. The basis is an oxidation mechanism where the rate determining step is the metal-carbon bond cleavage under acidic conditions which was supported by a detailed corrosion study on hexagonal tungsten carbide. In situ flow cell measurements that were coupled to an inductively coupled plasma mass spectrometer corroborated experimentally the linear dependency of the oxidation overpotential on the transition metal-carbon bond enthalpy. The proposed model allows the estimation of the activation overpotential for electrochemical carbide oxidation resulting in a maximized stabilization for carbides in the 4th group (Ti, Zr, Hf). Together with the calculated thermodynamic oxidation potentials, TiC and VC exhibit the highest experimental oxidation potentials (0.85 V-RHE). The model can be used for preselecting possible carbide materials for various electrochemical reactions. (C) 2020 The Author(s). Published on behalf of The Electrochemical Society by IOP Publishing Limited.
CRIS-Team WoS Importer:2020-01-24